Incidence of hypoglycaemia in the South African population with diabetes: results from the IDMPS Wave 7 study. Issue 2 (4th May 2019) - Kaplan, Hilton; Amod, Aslam; van Zyl, Francois H; Reddy, Jeevren; van Tonder, Alet; Tsymbal, Ellina; McMaster, Alicia
Abstract : Objectives: Management of diabetes is a balancing act of preventing a state of hyperglycaemia while avoiding episodes of hypoglycaemia. Limited information is currently available on the incidence of hypoglycaemia in South African people diagnosed with diabetes. Data regarding the management of diabetes and incidence of hypoglycaemia in the South African population was collected as part of Wave 7 of the International Diabetes Management Practices Study (IDMPS). Design and methods: During this observational study the first 10 adult individuals with type 2 diabetes and the first five adult individuals with type 1 diabetes presenting to a study site during the two-week study period were enrolled. Setting: Patients were enrolled from the private healthcare sector in South Africa only. Subjects: A total of 445 individuals (49 diagnosed with T1D, 396 diagnosed with T2D) were included. Outcome measures: Glycated haemoglobin and hypoglycaemia data were recorded for each patient. Results: Of the patients who reported experiencing hypoglycaemia, 48.6% (17/35) among T1D individuals and 67.8% (40/71) among T2D individuals experienced hypoglycaemia over a four-week period. Furthermore, in patients who discontinued insulin treatment ( n  = 11), fear of hypoglycaemia was reported to influence adherence to insulin treatment by 27.3% in T1D and T2D individuals. Of the 148 patients not achieving their HbA1c target, 23.0% reported fear of hypoglycaemia as a reason. Conclusions: This report demonstrates the need to address hypoglycaemia and fear of hypoglycaemia in the South African diabetes population.